Accuracy of three-dimensional soft tissue prediction for Le Fort I osteotomy using Dolphin 3D software: a pilot study. Issue 3 (March 2017) - Resnick, C.M.; Dang, R.R.; Glick, S.J.; Padwa, B.L.
Abstract: Three-dimensional (3D) soft tissue prediction is replacing two-dimensional analysis in planning for orthognathic surgery. The accuracy of different computational models to predict soft tissue changes in 3D, however, is unclear. A retrospective pilot study was implemented to assess the accuracy of Dolphin 3D software in making these predictions. Seven patients who had a single-segment Le Fort I osteotomy and had preoperative (T0 ) and >6-month postoperative (T1 ) cone beam computed tomography (CBCT) scans and 3D photographs were included. The actual skeletal change was determined by subtracting the T0 from the T1 CBCT. 3D photographs were overlaid onto the T0 CBCT and virtual skeletal movements equivalent to the achieved repositioning were applied using Dolphin 3D planner. A 3D soft tissue prediction (TP ) was generated and differences between the TP and T1 images (error) were measured at 14 points and at the nasolabial angle. A mean linear prediction error of 2.91 ± 2.16 mm was found. The mean error at the nasolabial angle was 8.1 ± 5.6°. In conclusion, the ability to accurately predict 3D soft tissue changes after Le Fort I osteotomy using Dolphin 3D software is limited.